2006
DOI: 10.1111/j.1365-2036.2006.02823.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetic acid‐enhanced magnification endoscopy in the diagnosis of specialized intestinal metaplasia, dysplasia and early cancer in Barrett's oesophagus

Abstract: SUMMARY BackgroundBarrett's surveillance is prone to sampling error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 24 publications
3
29
0
1
Order By: Relevance
“…While no randomised controlled trials for its use in the oesophagus exist, cohort studies have demonstrated effectiveness in the identification of dysplasia. The sensitivity for the identification of neoplasia has been suggested to be 71-100%, with a specificity between 80 and 99% (Vázquez-Iglesias et al 2007;Gossner et al 2005;Fortun et al 2006;Longcroft-Wheaton et al 2010). We believe that this is the dye of the future in the evaluation of Barrett's.…”
Section: Oesophageal Cancermentioning
confidence: 86%
“…While no randomised controlled trials for its use in the oesophagus exist, cohort studies have demonstrated effectiveness in the identification of dysplasia. The sensitivity for the identification of neoplasia has been suggested to be 71-100%, with a specificity between 80 and 99% (Vázquez-Iglesias et al 2007;Gossner et al 2005;Fortun et al 2006;Longcroft-Wheaton et al 2010). We believe that this is the dye of the future in the evaluation of Barrett's.…”
Section: Oesophageal Cancermentioning
confidence: 86%
“…Chromoendoscopy uses a stain (eg, methylene blue, Lugol's iodine, crystal violet, or acetic acid) that is applied with a spray catheter. The stain highlights the mucosal pit pattern, which can distinguish BE from squamous mucosa, and in conjunction with magnification, endoscopy appears to be accurate for neoplasia [32,33]. Narrow-band imaging uses a higher intensity of blue light than found in white light, highlighting the pit pattern (similarly to chromoendoscopy) and the vascular pattern.…”
Section: Novel Endoscopic Imaging Techniquesmentioning
confidence: 96%
“…Magnification endoscopy allows for detailed visualization of the mucosal surface; an irregular or distorted pit pattern appears to be closely associated with high-grade dysplasia or cancer [32,33]. Confocal laser microscopy also magnifies the mucosa and allows for visualization up to 250 m below the surface.…”
Section: Novel Endoscopic Imaging Techniquesmentioning
confidence: 99%
“…This is a difficulty highlighted by this case study. There has been interest in using endoscopic dyes (methylene blue and acetic acid) to target biopsies in order to increase the yield of IM and dysplasia in the sampling material; however, the results have been disappointing except in expert hands (Canto et al, 2001;Fortun et al, 2006). New imaging technologies [narrow-band imaging (NBI) and autofluorescence] have recently been introduced to improve the diagnostic power of endoscopy.…”
Section: Early Diagnosis and Biomarkers Of Progressionmentioning
confidence: 99%